Induced sputum inflammatory mediator concentrations in eosinophilic bronchitis and asthma - Brightling, C; Ward, R; Woltmann, G; Bradding, P; Sheller, JR; Dworski, R; Pavord, I (2000)
Eosinophilic bronchitis is a common cause of chronic cough, which like asthma is characterized by sputum eosinophilia, but in contrast to asthma there is no variable airflow obstruction or airway hyperresponsiveness. Our hypothesis was that the differences in airway pathophysiology maybe due to less active airway inflammation in eosinophilic bronchitis, with reduced release of important effector mediators. We measured the concentration of various proinflammatory mediators in induced sputum cell-free supernatant in eight patients with eosinophilic bronchitis, 17 patients with asthma matched for sputum eosinophil count, and 10 normal subjects. Cysteinyl-leukotrienes (cys-LT) were measured by enzyme immunoassay, eosinophilic cationic protein (ECP) by fluoroimmunoassay, prostanoids (PGE2, PGD2, TXB2, and PGF(2α)) by gas chromatography-negative ion chemical ionization-mass spectroscopy, and histamine by radioenzymic assay. The geometric mean sputum eosinophil count was similar in asthma (13.4%) and eosinophilic bronchitis (12.5%). Sputum cys-LT and ECP were a mean (95% CI) 1.6-fold (1.1, 2.5) and 6.4-fold (1.4, 28) higher in eosinophilic bronchitis and 1.9-fold (1.3, 2.9) and 7.7-fold (1.2, 46) higher in asthma compared with that in control subjects (geometric mean, 5.9 and 95 ng/ml, respectively). In eosinophilic bronchitis the mean concentration of sputum PGD2 (0.79 ng/ml) and histamine (168 ng/ml) were significantly higher than in asthma (mean absolute difference in PGD2 concentration, 0.47 ng/ml [95% CI, 0.19 to 0.74] and mean-fold difference in histamine concentration, 6.7 [95% CI 1.7 to 26]) and normal subjects (0.64 ng/ml [0.36 to 0.90] and 11-fold [3.3 to 36]), respectively. In conclusion, eosinophilic bronchitis is associated with active airway inflammation with increased release of vasoactive and bronchoconstrictor mediators.